Corruption and Governance: Evidence from Southeast Asian Countries - Fred-Jaiyesimi (International Journal of Law and Political Authority, 2026)
This article examines the relationship between corruption and governance in Southeast Asian countries through a comparative and sectoral perspective. Drawing on prior empirical research, official reports, and institutional analyses, the study explores how variations in governance quality shape corruption dynamics across political, administrative, and economic domains. The findings indicate that corruption is sustained not solely by weak legal frameworks but by structural governance deficiencies, including limited institutional autonomy, selective enforcement, and entrenched political economic networks. Sectoral evidence from health services, education, public procurement, environmental governance, and corporate regulation demonstrates that governance failures translate directly into reduced service quality, fiscal inefficiency, and constrained development outcomes. Comparative analysis of anti corruption policy instruments further reveals that reforms achieve meaningful impact only when embedded within coherent governance systems characterized by accountability, transparency, and rule of law credibility. The study contributes to governance scholarship by highlighting the limits of fragmented reform approaches and emphasizing the centrality of institutional integrity in corruption control. These findings offer policy-relevant insights for designing context-sensitive and sustainable governance reforms in Southeast Asia..